GAMBARAN PENGETAHUAN GURU SEKOLAH DASAR MENGENAI TAHAPAN PERKEMBANGAN ANAK DALAM ASPEK FISIK, KOGNITIF, PSIKOSOSIAL, DAN SEKSUAL DI SD X - Hernilen Hernilen; Margaretha Purwanti (MANASA, 2014)
Nowadays, just a few elementary schools have sexual education programfor their students. One of school that had not a consistent sexual education fortheir students is SD X. Teachers have difficulties determining the appropriatematerial, as it is not regulated in the curriculum, whereas teachers have a central role in planning and delivering sexual education program. Teachers, amongst the others in school, know their student best, their age and stage of developments, their families and their learning needs. The purpose of this study is to gain a descriptive review of SD X teachers’ knowledge about children stage of development in physical, cognitive, psychosocial, and sexual aspects. Instrument tools used in this study is questionnaires and group interviews to homeroom and subject teachers. Result from this study is teachers’ knowledge about the children developmental stages currently at quite adequate level, but not been evenly distributed in the four aspects measured. Therefore, teachers need to be given a short training about school age developmental stages and the appropriate sexual education program for elementary school.